Facile photochemical synthesis of graphene-Pt nanoparticle composite for counter electrode in dye sensitized solar cell - Tjoa, Verawati (2013)
A low temperature route to synthesize graphene oxide–Pt nanoparticle hybrid composite by light assisted spontaneous coreduction of graphene oxide and chloroplatinic acid without reducing agent is demonstrated. Analysis indicates the importance of light as energy provider and ethanol as hole scavenger in the formation of small Pt nanoparticles (3 nm) on graphene oxide as well as graphene oxide reduction. Spray coating was used to deposit the hybrid material as a counter electrode in dye sensitized solar cells (DSCs). An efficiency of 6.77% for the hybrid graphene counter electrode has been obtained, higher than the control device made by low temperature sputtered Pt as counter electrode. Compatibility of the hybrid material with flexible plastic substrates was demonstrated yielding DSCs of an efficiency of 4.05%.